The Role of Notarial Deeds in Avoiding Default on Debt Agreements: Peran Akta Notaris dalam Menghindari Wanprestasi pada Perjaanjian Utang Piutang - Saputra, Ardiansyah; Djajaputra, Gunawan (Indonesian Journal of Law and Economics Review, 2025)
General Background: Debt–credit agreements constitute a common legal instrument in civil and commercial transactions, yet remain vulnerable to default, which often triggers disputes and economic losses. Specific Background: Notarial deeds are legally recognized as authentic instruments that provide preventive and evidentiary strength in structuring such agreements. Knowledge Gap: However, limited scholarly attention has been given to examining how notarial intervention substantively reduces the risk of wanprestasi and strengthens creditor protection. Aims: This study aims to analyze the preventive role of notaries in drafting balanced loan agreements and to evaluate how authentic deeds reinforce creditors’ legal standing in cases of default. Results: Findings show that notaries not only ensure the legal validity and proportionality of contractual clauses but also provide legal certainty through authentic deeds that permit direct execution without complex litigation. Novelty: This research highlights the dual preventive–executory function of notarial deeds, demonstrating their critical contribution to both dispute avoidance and expedited enforcement. Implications: Strengthening notarial practice and public awareness of authentic deeds can significantly enhance legal protection in loan agreements, reduce default risks, and promote a more secure civil transaction environment. Highlights: Notarial deeds function preventively by ensuring balanced and lawful clauses in debt–credit agreements. Authentic notarial deeds give creditors strong evidentiary power and enable direct execution in cases of default. Strengthening notarial practice and public awareness reduces dispute risk and enhances legal certainty in civil transactions. Keywords: Debt–Credit Agreement, Notarial Deed, Default (Wanprestasi), Creditor Protection, Authentic Instrument